Pan‐cancer analyses reveal molecular and clinical characteristics of cuproptosis regulators. Issue 1 (7th December 2022) - Wu, Changwu; Tan, Jun; Wang, Xiangyu; Qin, Chaoying; Long, Wenyong; Pan, Yimin; Li, Yuzhe; Liu, Qing
Abstract: Imbalance in copper homeostasis can be lethal. A recent study found that excess copper induces cell death in a way that has never been characterized before, which is dependent on mitochondrial stress and is referred to as "cuproptosis." The role of cuproptosis in tumors has not yet been elucidated. In this study, we revealed the complex and important roles of cuproptosis regulators and cuproptosis activity in tumors via a comprehensive analysis of multiomics data from more than 10, 000 samples of 33 tumor types. We found that the cyclin‐dependent kinase inhibitor 2A is the most frequently altered cuproptosis regulator, and the cuproptosis regulator expression is dysregulated in various tumors. Additionally, we developed a cuproptosis activity score to reflect the overall cuproptosis level. On the basis of the expression levels of cuproptosis regulators, tumors can be divided into two clusters with different cuproptosis activities and survival outcomes. Importantly, cuproptosis activity was found to be associated with the prognosis of multiple tumors and multiple tumor‐related pathways, including fatty acid metabolism and remodeling of the tumor microenvironment. Furthermore, cuproptosis increased the sensitivity to multiple drugs and exhibited potential to predict the outcome of immunotherapy. We also comprehensively identified cuproptosis‐related microRNAs, long noncoding RNAs, and transcription factors. We provided the code corresponding to the results of this study in GitHub (https://github.com/Changwuuu/Cuproptosis-pancancer.git ) for reference. In summary, this study reveals important molecular and clinical characteristics of cuproptosis regulators and cuproptosis activity in tumors, and suggests the use of cuproptosis as a promising tumor therapeutic approach. This study provides an important reference point for future cuproptosis‐related research. Abstract : We developed a cuproptosis activity score to reflect the overall cuproptosis level, which could provide a methodological reference for future cuproptosis studies. Cuproptosis is associated with a variety of tumor‐related pathways, and in particular, tumors with high fatty acid metabolism may be more sensitive to cuproptosis. Cuproptosis is associated with the regulation of the tumor microenvironment and can predict the outcome of immunotherapy patients based on cuproptosis activity. This study identified cuproptosis‐related microRNAs, long noncoding RNAs, and transcription factors in each tumor type, which can provide a resource and reference for future cuproptosis‐related research. Highlights: We developed a cuproptosis activity score to reflect the overall cuproptosis level, which could provide a methodological reference for future cuproptosis studies. Cuproptosis is associated with a variety of tumor‐related pathways, and in particular, tumors with high fatty acid metabolism may be more sensitive to cuproptosis. Cuproptosis is associated with the regulation of the tumor microenvironment and can predict the outcome of immunotherapy patients based on cuproptosis activity. This study identified cuproptosis‐related microRNAs, long noncoding RNAs, and transcription factors in each tumor type, which can provide a resource and reference for future cuproptosis‐related research.